The effects of adding different whole-body vibration frequencies to preconditioning exercise on subsequent sprint performance - Ronnestad, B. R.; Ellefsen, S. (The Journal of Strength and Conditioning Research, 2011)
The phenomenon postactivation potentiation can possibly be used to acutely improve sprint performance. The purpose of this study was to investigate the effect of adding whole-body vibration (WBV) to body-loaded half-squats, performed as preconditioning activity to the 40-m sprint test. Nine male amateur soccer players performed 1 familiarization session and 6 separate test sessions. Each session included a standardized warm-up followed by 1 of the after preconditioning exercises: 30-seconds of half-squats with WBV at either 50 or 30 Hz or half-squats without WBV. The 40-m sprint was performed 1 minute after the preconditioning exercise. For each subject, each of the 3 protocols was repeated twice on separate days in a randomized order. Mean values were used in the statistical analysis. Performing the preconditioning exercise with WBV at a frequency of 50 Hz resulted in a superior 40-m sprint performance compared to preconditioning exercise without WBV (5.48 ± 0.19 vs. 5.52 ± 0.21 seconds, respectively, p < 0.05). There was no difference between preconditioning exercise with WBV at a frequency of 30 Hz and the no-WBV condition. In conclusion, preconditioning exercise performed with WBV at 50 Hz seems to enhance 40-m sprint performance in recreationally trained soccer players. The present findings suggest that coaches can incorporate such exercise into the warm-up to improve sprint performance or the quality of the sprint training.